Risk factors for non-optimal breastfeeding practices in low birth weight infants - Ekawaty L Haksari; Setya Wandita; Yustivani Yustivani (Indonesian Pediatric Society Publishing House, 2010)
Background Low birth weight infants are ongoing problems since they are likely to have high risks of morbidity, mortality and feeding problems. American Academy of Pediatrics recommends breastfeeding practice for infants with low birth weight, yet some problems have occured. Objective To determine risk factors for non-optimal breastfeeding practices in low birth weight infants. Methods In this historical cohort study we included mothers with 6-month-old infants, single birth with weight of2000-2499 grams and the pregnancy period of 2:: 34 weeks, and excluded mothers with infants who had a major congenital disorder, labioschizis, labiognatopalatoschizis, or history of admission in NICU. Data were collected using standard longitudinal surveillance form for breastfeeding mothers. Analyses were performed using chi-square test and logistic regression. Results The percentage of low birth weight infants breastfed optimally were 42.7%. Working mothers presented the highest risk for non-optimal breastfeeding. The onset of lactation for more than 6 hours was the second factor (81.8%). The results of multivariate logistic regression analysis showed that mothers who worked (RR 2.79; 95% CI 1.84 to 4.23) and onset lactation of more than 6 hours (RR 2.34; 95% CI 1.57 to 3.50) were the risk factors for non-optimal breastfeeding practices in low birth weight infants. Conclusion Mother's working status and onset of lactation for more than 6 hours were the risk factors for non-optimal breastfeeding in low birth weight infants.